Structural Bamboo Building Codes: Catalysts for Industry, Research, and Construction Technology. Issue 1 (2nd January 2019) - Witte, David
Abstract : On April 16, 2016, a magnitude 7.8 earthquake destroyed over 35, 000 homes along the Pacific coast of Ecuador, leaving more than 140, 000 people without permanent housing. However, bamboo houses proved resilient to the seismic forces, prompting a reevaluation of the material and the creation of an Ecuadorian bamboo building code. Public, private, and academic initiatives are addressing industry challenges and developing improved bamboo construction methods that are rebranding the stigmatized material. This research documents improvements to the bamboo supply chain in Peru and Ecuador through interviews conducted with architects, engineers, and agroforestry experts across the region. The results highlight hybridized solutions that are propelling the industry toward standardizing its practices and scaling structural bamboo housing from a disaster reconstruction strategy toward mainstream use across South America.